Profesionalisme Militer pada Pemerintahan Soeharto dan Abdurrahman Wahid: Kajian Perbandingan Sosial-Historis - Mohammad Siddiq (Universitas Islam Darul Ulum Lamongan, 2019)
The reforms that rolled out in 1998 were one of the important momentum in the history of civil-military relations in Indonesia. The thick political and bureaucratic culture of military domination in the 32 years of Soeharto's reign with Dwi The function of his ABRI turned to Abdurrahman Wahid's government which put forward civilian supremacy especially in terms of politics and bureaucracy to be interesting to discuss. This study is a comparison of the role of the military during the Soeharto government and Abdurrahman Wahid's administration with a historical social qualitative approach. The findings indicate that the New Order government regime tended to be authoritarian in that the power rested on one President who was able to control military power to maintain power, whereas during Abdurrahman Wahid's administration system tended to shift towards a more democratic regime. Through this study, it can be concluded that in the transition to a democratic regime, restructuring the role of the military in political life is an important prerequisite that must be carried out.